Summary of the 2019 BMT CTN Myeloma Intergroup Workshop on Minimal Residual Disease and Immune Profiling - Holstein, Sarah A. (Biol Blood Marrow Transplant, 2020)
The Blood and Marrow Transplant Clinical Trials Network (BMT CTN) Myeloma Intergroup has organized an annual workshop focused on minimal residual disease (MRD) testing and immune profiling (IP) in multiple myeloma since 2016. In 2019, the workshop took place as an American Society of Hematology (ASH) Friday Scientific Workshop entitled “Immune Profiling and Minimal Residual Disease Testing in Multiple Myeloma”. This workshop focused on four main topics: the molecular and immunological evolution of plasma cell disorders, the development of new laboratory- and imaging-based MRD assessment approaches, chimeric antigen receptor T-cell therapy research, and the statistical and regulatory issues associated with novel clinical endpoints. In this report, we provide a summary of the workshop and discuss future directions.